Strategi Penataan Ruang Perdesaan Dalam Menghadapi Era Globalisasi - Uton Rustan Harun (Journal of Regional and City Planning, 1995)
The import substitution strategy and continuous efforts to promote foreign investment, capital and advanced technology tends to concentrate the industrial investment in the core of region. Although varied in degree and in a broad sense. the strategy of growth-pole theory is an inevitable approach in regional planning for many developing countries facing the challenge of global economic. The serious consequences of this approach is the ever widening regional disparities and polarization of capital, industries and conglomeration in one or few elite group. Evaluation and re-examination of this strategy for the regional development in Indonesian are important. Exploration of a new paradigm in regional planning is challenging and re-orientation to the rural development strategy is not a faulty thought.